Systemic administration of strontium ranelate to enhance the osseointegration of implants: systematic review of animal studies - Scardueli, Cassio Rocha [UNESP]; Bizelli-Silveira, Carolina; Marcantonio, Rosemary Adriana C. [UNESP]; Marcantonio, Elcio [UNESP]; Stavropoulos, Andreas; Spin-Neto, Rubens (Springer, 2018)
The literature states that Strontium (Sr) is able to simultaneously stimulate bone formation and suppress bone resorption. Recent animal studies suggest that the systemic administration of Sr, in the form of strontium ranelate (SRAN), would enhance the osseointegration of implants. The purpose of the present study was to undertake a systematic review on animal studies evaluating the systemic administration of Sr to enhance the osseointegration of titanium implants and the remodeling of bone grafts. The MEDLINE (PubMed) and Scopus bibliographic databases were searched from 1950 to October 2017 for reports on the use of systemic and non-radioactive Sr to enhance the osseointegration of titanium implants and the remodeling of bone grafts in animals. The search strategy was restricted to English language publications using the combined terms: strontium and implant or graft or biomaterial or bone substitute. Five studies were included, all related to the systemic administration of Sr in the form SRAN, and its effects on osseointegration of titanium implants. No studies on the use of SRAN-based therapy to enhance the remodeling of bone grafts were found. The studies differed notably with respect to the study population (healthy female rats, healthy male rats, and female rats with induced osteoporosis) and SRAN dose (ranging from 500 to 1000 mg/kg/day). Results were diverse, but a tendency suggesting positive influence of systemic SRAN administration on the osseointegration of titanium implants was observed. No major side-effects due to strontium administration were reported. Systemic Sr administration, in the form of SRAN, seems to enhance peri-implant bone quality and implant osseointegration in animals, however, at a moderate extent. Further studies, evaluating both the effects of this drug on implant osseointegration and the risk/benefit of its use, are needed to provide a rationale of this therapeutic approach.
Keywords: Strontium; Systemic use; Osseointegration; Bone remodeling